2021
DOI: 10.2196/23251
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Patients With COVID-19 in India by Demographic Factors: Quantitative Study

Abstract: Background Studies of the transmission dynamics of COVID-19 have depicted the rate, patterns, and predictions of cases of this pandemic disease. To combat transmission of the disease in India, the government declared a lockdown on March 25, 2020. Even after this strict lockdown was enacted nationwide, the number of COVID-19 cases increased and surpassed 450,000. A positive point to note is that the number of recovered cases began to slowly exceed that of active cases. The survival of patients, taki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
2
0
1
Order By: Relevance
“…This study revealed that older age (greater than 60 years) was associated with mortality among COVID-19 patients, a finding that is consistent with studies that also reported that old age has an increased risk of dying from COVID-19 [ 8 , 10 12 , 14 , 16 , 20 , 35 ]. This could be attributed to the fact that the body’s immune system particularly the cell mediated immunity deteriorates with age and also the presence of comorbidities that make older persons more prone to severe COVID-19 disease and eventually death [ 36 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study revealed that older age (greater than 60 years) was associated with mortality among COVID-19 patients, a finding that is consistent with studies that also reported that old age has an increased risk of dying from COVID-19 [ 8 , 10 12 , 14 , 16 , 20 , 35 ]. This could be attributed to the fact that the body’s immune system particularly the cell mediated immunity deteriorates with age and also the presence of comorbidities that make older persons more prone to severe COVID-19 disease and eventually death [ 36 ].…”
Section: Discussionsupporting
confidence: 90%
“…Majority of the patients have asymptomatic to mild COVID-19 disease and about 15% of the COVID-19 patients suffered severe illness which presented as need for hospitalization, supplemental oxygen or mechanical ventilation [6,7]. A number of studies conducted in mostly high income countries have revealed that the factors associated with severe COVID-19 illness and mortality are older age, male gender, and having comorbidities such as hypertension, diabetes, cardiovascular diseases and respiratory diseases [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Low-income countries could have unique factors associated with mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian ini menyimpulkan bahwa tidak terdapat perbedaan peluang sembuh antara pasien laki-laki dengan pasien perempuan. Analisis survival pasien COVID-19 juga dilakukan di India dengan menggunakan kematian sebagai event dari penelitian dan menguji kesamaan fungsi survival berdasarkan kelompok umur dan jenis kelamin [8]. Ketiga peneliti tersebut membandingkan fungsi survival data waktu dengan metode Kaplan-Meier tetapi tidak menganalisis faktor-faktor (kovariat) yang memengaruhinya.…”
Section: Siti Fatimah Khairunnisa Suyitno Siti Mahmudaunclassified
“…To assess attributes that might be related to the mortality and symptoms of COVID-19 patients, many studies have employed conventional survival methods, such as the Kaplan-Meier estimator and Cox model. Among them, [21], [24], and [31] used the Cox model and identified age as a common risk factor significantly affecting hazard rates. In addition, in the model, they included other risk factors, such as demographics, including sex and region, and laboratory measurements, such as white blood cell count and albumin levels, as well as the presence of certain chronic diseases.…”
Section: Literature Reviewmentioning
confidence: 99%